1998
DOI: 10.1021/jp972267z
|View full text |Cite
|
Sign up to set email alerts
|

Size Effect of α,ω-Diphenylpolyenes on the Formation of Nanotubes with γ-Cyclodextrin

Abstract: We have studied the size effect of the homologues of the R,ω-diphenylpolyenes series, with two, three and four double bonds, on the formation of nanotubes with γ-cyclodextrin. The data show that only the two longest polyenes facilitate the formation of tubular structures when mixed with the γ-cyclodextrin in the appropriate solvent, while the average length of these nanotubes increases with increasing size of the diphenylpolyenes. Using computer simulations, we have examined the processes by which nanotubes fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 18 publications
2
44
0
1
Order By: Relevance
“…The hypsochromic shift of the fluorescence maxima and the concomitant increase in the fluorescence intensity confirm the encapsulation of the guest molecule inside the hydrophobic cavity of c-CD (explained elsewhere in details) [29,30]. We tested for the nature of encapsulation of DMASBT inside the CD cavity using the Benesi-Hildebrand double reciprocal method [5][6][7][8][9][10][11]. However, this method is not suitable for the systems where there is a possibility of nanotube formation, since this is a multi-step process [5][6][7][8].…”
Section: Fluorometric Changes Of Dmasbt Due To Encapsulationmentioning
confidence: 67%
See 2 more Smart Citations
“…The hypsochromic shift of the fluorescence maxima and the concomitant increase in the fluorescence intensity confirm the encapsulation of the guest molecule inside the hydrophobic cavity of c-CD (explained elsewhere in details) [29,30]. We tested for the nature of encapsulation of DMASBT inside the CD cavity using the Benesi-Hildebrand double reciprocal method [5][6][7][8][9][10][11]. However, this method is not suitable for the systems where there is a possibility of nanotube formation, since this is a multi-step process [5][6][7][8].…”
Section: Fluorometric Changes Of Dmasbt Due To Encapsulationmentioning
confidence: 67%
“…Li and co-workers found that nanotubes of b-and c-CD incorporated with a rod-like molecule could be formed just through supramolecular assembly [5]. Pistolis and co-workers studied in extension to the findings of Li et al and corroborated the results by investigating the size-effect of certain molecular homologues on the formation of nanotubes with c-CD [10,11]. a-, b-and c-CDs are known to undergo self-aggregation in aqueous solution [12].…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Li and his co-workers found that nanotubes of β-and γ -CD incorporated with a rod-like molecule, i.e., all-trans-1,6-diphenyl-1,3,5-hexatriene (DPH) could be formed just through supramolecular assembly [7]. Later, Pistolis et al corroborated the results by a detailed study on the size effect of the homologues of the α,ω-diphenylpolyebes series, with two, three and four double bonds, on the formation of nanotubes with γ -CD [8,9]. Agbaria and Gill discovered that some oxazole molecules could also lead to the formation of nanotubes of γ -CD in aqueous solutions [10][11][12].…”
Section: Introductionmentioning
confidence: 94%
“…Pistolis et al found that DPH could facilitate the formation of nanotubes with b-and c-CD in the appropriate solvents [4]. The results of their further study on the size effect of the homologues of the a,x-diphenylpolyenes series, with two, three, and four double bonds, on the formation of nanotubes with c-CD indicated that the length of guest molecule is a key factor in the course of nanotube formation [5]. Liu et al focused on the artificial design of CD nanotubes induced by different CD derivatives and metal ions through the metal-ligand coordination [6][7][8].…”
Section: Introductionmentioning
confidence: 99%